European Financial Markets - Southall, Tony (Springer, 2017)
EU membership involves political and economic reforms which influence financial markets in the new member states. This study empirically explores and quantifies the effects of EU accession on the risk and return of equity markets in eight Central and Eastern European markets joining the EU in 2004. The study also incorporates a review of how the influence of macroeconomic variables and the level of integration with global and European markets change as a result of EU membership. Based on empirical tests using weekly data over ten years, this study concludes that EU membership results in a significant decline in equity market volatility and a significant increase in risk-adjusted, but not absolute, equity returns. Furthermore, the study suggests that equity markets in new EU member states become increasingly influenced by global rather than local macroeconomic factors after the EU accession and that the level of integration with global markets increases.